Childhood vaccination practices and associated factors among mothers/caregivers in Debre Tabor town, Northwest Ethiopia: A cross-sectional study - Wudneh Simegn; Mengistie Diress; Yibeltal Yismaw Gela; Daniel Gashaneh Belay; Daniel Gashaneh Belay; Anteneh Ayelign Kibret; Dagmawi Chilot; Dagmawi Chilot; Deresse Sinamaw; Mohammed Abdu Seid; Amare Agmas Andualem; Desalegn Anmut Bitew; et al. (Frontiers Media S.A., 2023)
BackgroundIncomplete immunization and non-immunization increase the risk of disease and death among children. This study aims to assess childhood vaccination practices and associated factors among mothers and caregivers in Debre Tabor town, Amhara region, Ethiopia.MethodsA community-based cross-sectional study design was conducted between February 30 and April 30, 2022. The study participants were proportionally allocated to all six kebeles found in the town. A systematic random sampling technique was used to select the study participants. The collected data were checked and coded and then entered into EpiData Version 3.1 and exported into SPSS Version 26. The results were organized using frequency tables, graphs, and charts, and bivariate and multivariable logistic regression were used to test the association of covariates with childhood vaccination practices.ResultApproximately 422 study mothers and caregivers participated in the study, with a response rate of 100%. The mean age was 30.63 years (11.74), which ranged from 18 to 58 years. More than half of the study participants (56.4%) expressed fears about the side effects of vaccination. A majority (78.4%) of the study participants availed of counseling services about vaccination, and 71.1% of them received regular antenatal care. This study found that approximately 280 [66.4%, 95% confidence interval (CI): 61.8-70.6] mothers/caregivers had a history of good childhood vaccination practices. The factors of the fear of side effects [adjusted odds ratio (AOR) = 3.34; 95% CI: 1.72-6.49], no workload (AOR = 6.08; 95% CI: 1.74-21.22), medium workload (AOR = 4.80; 95% CI: 1.57-14.71), being a mother of child/children (AOR = 2.55; 95% CI: 1.27-5.13), positive attitude (AOR = 2.25; 95% CI: 1.32-3.82), and sound knowledge (AOR = 3.88; 95% CI: 2.26-6.68) were significantly associated with childhood vaccination practices.ConclusionMore than half of the study participants had a history of good childhood vaccination practices. However, the rate of such practices was low among mothers and caregivers. The fear of side effects, workload, motherhood, attitude, and knowledge were all factors associated with childhood vaccination practices. Awareness creation and a consideration of the workload of mothers would be helpful in dispelling fears and increasing the rate of good practices among mothers and caregivers.